Overview of the Use of Leisure Time for the Elderly - Livya Apriani Rukmana; Kartinah Kartinah (Indonesian Journal of Global Health Research, 2025)
The elderly is someone who is ≥60 years old. In Indonesia, which has entered the old structured phase, it must be balanced with an effective quality of life. Therefore, an effort needs to be made, namely, taking advantage of leisure. Leisure is used to relax, entertain, or develop skills to obtain happiness. This study aims to describe the use of leisure for the elderly at the Gambirsari Health Center. This study used a quantitative descriptive design with a purposive sampling technique involving 98 elderly people who met the research criteria. The research data was measured using a questionnaire analyzed univariately using frequency and percentage distributions. The study results showed that 56.1% of respondents made good use of their leisure time. Based on each domain, in the religious domain, 56.1% of respondents utilized their leisure in the good category; in the social domain, 67.3% of respondents utilized their leisure in the sufficient category; and in the hobby domain, 54.1% of respondents utilized their leisure in the sufficient category. In conclusion, leisure for the elderly at the Gambirsari Health Center is dominated by the good category.